PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN MOBIL TOYOTA AVANZA VELOZ DI PT. CHANDRA PRATAMA MOTOR PEKALONGAN - Fatkhul Hadi, 14.05.51.0217 (Students' Journal of Economic and Management, 2018)
This study examines the effect of product quality, brand image and price perception on the purchasing decision process. This research is a quantitative research, which uses primary data and secondary data. The population in this study were all consumers who bought a Toyota Avanza Veloz car at PT. Chandra Pratama Motor Pekalongan in 2013 - 2017 with a total of 692 people and the number of samples taken was 100 respondents. Sampling is done by using probability sampling (random sample) method. Instrument collection techniques using questionnaires distributed directly to respondents. The results of this study indicate that product quality and brand image have a positive and significant effect on the purchase decision process while the perception of price does not affect the purchase decision process. Keywords: Purchasing decision process, Product quality, Brand image, Price perception